2019
DOI: 10.1103/physreva.100.013818
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of localized structures by inhomogeneous injection in Kerr resonators

Abstract: We consider the formation of temporal localized structures or Kerr comb generation in a microresonator with inhomogeneities. We show that the introduction of even a small inhomogeneity in the injected beam widens the stability region of localized solutions. The homoclinic snaking bifurcation associated with the formation of localized structures and clusters of them with decaying oscillatory tails is constructed. Furthermore, the inhomogeneity allows not only to control the position of localized solutions, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The paper is organized as follows, after a brief introduction, we discuss in Section 2 , the formation of dissipative solitons in the presence of inhomogeneities. This effect has been discussed in [17] for a small and positive defect, here we investigate more systematically the effect of inhomogeneities including the case when the amplitude of the defect is negative. We analyze this effect by using the tools of bifurcation theory, showing that depending on the system parameters, the inhomogeneity can attract or repeal dissipative solitons.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The paper is organized as follows, after a brief introduction, we discuss in Section 2 , the formation of dissipative solitons in the presence of inhomogeneities. This effect has been discussed in [17] for a small and positive defect, here we investigate more systematically the effect of inhomogeneities including the case when the amplitude of the defect is negative. We analyze this effect by using the tools of bifurcation theory, showing that depending on the system parameters, the inhomogeneity can attract or repeal dissipative solitons.…”
Section: Introductionmentioning
confidence: 91%
“…When the Kerr resonators are driven by an inhomogeneous injected beam such as a modulated beam [13][14][15] or Gaussian [16] , dissipative solitons can be stabilized through the front pinning mechanism. When the cavity is operating close to the modulational instability, it has been shown that the inhomogeneity impacts strongly the stability domains, as well as the homoclinic snaking bifurcation associated with the formation of dissipative solitons [17] . In particular, the stability domain of a single peak dissipative solitons is much larger than the pinning region where the system exhibits multistability between multiple peaks of dissipative solitons [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that CSs in Kerr resonators driven with pulsed or amplitude modulated fields are attracted to (and subsequently pinned to) temporal positions associated with specific values of the driving field amplitude [33] -behaviour that is in stark contrast to the tendency of CSs to be attracted to the extrema of phase inhomogeneities [23,30,31]. Moreover, Tabbert et al have shown that amplitude inhomogeneities can affect the domains of soliton existence and stability [34]. The analyses reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses reported in Refs. [33] and [34] were, however, performed under the assumption of perfect synchronization between the CS(s) and the periodic driving field, which is unlikely to hold true in general.…”
Section: Introductionmentioning
confidence: 99%